New Studies on the Cave Paintings of the Selvascura Hermitage at the Sanctuary of the Crucifix in Bassiano (Latina) (Fenestella. Inside Medieval Art, 2022)
This article aims to re-examine the frescoes in the Selvascura hermitage in Bassiano, one of the medieval pictorial contexts created in caves in Lower Lazio, both from an iconographic and stylistic point of view. In the past, the paintings aroused some attention from local connoisseurs, but they collected a barely timid interest in critical publications.The carried out research revealed the existence of a link between the iconographic choices made in the cave paintings and the Greek theological literature, especially the Heavenly Ladder of St. John Climacus, known by the Franciscan Spirituals thanks to the translations by Angelo Clareno. Therefore, it is possible to suggest a new iconological interpretation of the frescoes on the right side of the cave and to overcome the traditional approach that considered the decoration of this hermitage as a mere juxtaposition of votive panels. Furthermore, an unpublished painting inspired by one of the apologues told by Barlaam to the Indian prince Josaphat has been identified and it can be added to the small list of monumental works with this theme related to the Italian Middle Age. This paper explains also all the documents from the current archives of the Soprintendenza concerning these frescoes and their preservative history from the 70s to the 90s of the XX century.Finally, an accurate analysis of the stylistic features and the comparison with other pictorial and mosaic works from Rome and the rest of Lazio allow to date back the paintings to the period between the end of the 13th and the beginning of the 14th century and to recognize the style of unknown artists trained in the school of Cavallini, very close to the Magister Conxolus’s lesson.
Keywords: Bassiano cave; Angelo Clareno; Heavenly Ladder; Franciscan Spirituals; Barlaam and Josaphat